2021
DOI: 10.1002/cb.2015
|View full text |Cite
|
Sign up to set email alerts
|

Combating the fear of COVID‐19 through shared accommodations: Does perceived human presence create a sense of social connectedness?

Abstract: Among other shared systems, sharing accommodations offer several social benefits. Although previous work has mainly focused on social means to fulfill connectedness needs, in this research, we demonstrate that such needs can be satisfied through symbolic means. As such, we explore how human presence (a sense of personalness and warmth of a human being) can be conveyed in shared accommodations through personalized decorative elements, without any actual human presence. Across four studies (two surveys and two e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 67 publications
(117 reference statements)
0
12
0
Order By: Relevance
“…Recent studies have shown that vehicle ownership among younger people has been declining and these technology-savvy consumers are keen to explore alternative modes of transportation (Bernardi, 2018; Lavieri et al ., 2017; Menon et al ., 2019). In fact, the sharing economy has been shown to provide numerous social benefits and fostering social connectedness among its users (Dogerlioglu-Demir et al , 2021; Liang et al , 2021).…”
Section: Perceived Relative Advantagementioning
confidence: 99%
“…Recent studies have shown that vehicle ownership among younger people has been declining and these technology-savvy consumers are keen to explore alternative modes of transportation (Bernardi, 2018; Lavieri et al ., 2017; Menon et al ., 2019). In fact, the sharing economy has been shown to provide numerous social benefits and fostering social connectedness among its users (Dogerlioglu-Demir et al , 2021; Liang et al , 2021).…”
Section: Perceived Relative Advantagementioning
confidence: 99%
“…Please also note that in Turkey, where we conducted our study, COVID-19 policies have been moderately stringent. For instance, certain workplaces, schools, and recreational areas were closed, yet travel was allowed with proof of accommodation reservations (Dogerlioglu-Demir et al, 2021 ; Hale, et al, 2021 ). Even in the beginning of the pandemic (January 2020), the rate of use of masks was high though there was no legal obligation to do so (60% of those surveyed wore masks when in public) (Akdeniz et al, 2020 ).…”
Section: Methodsmentioning
confidence: 99%
“…In the case of the latter two examples above, the results are consistent with a related form of magical thinking known as trait transference. Additionally, Dogerlioglu‐Demir et al (2022) found that imbuing a shared accommodation with human presence decreases the fear of contracting COVID‐19.…”
Section: Theoretical Backgroundmentioning
confidence: 99%